Effect of Ethepon as Ripening Stimulant on The Quality of Barangan Banana (Musa paradisiaca L) Fruit - Shahila Putri Ridhyanty; Elisa Julianti; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Posharvest handling is an attemp to meet market demand of agricultural products ideal condition. This reaserch was conducted to determine the effect of ethepon on the quality of barangan banana using complete randomized design consisting of two factors, i.e the maturity of barangan banana (M) : (75-80% and 85-90%) and ethepon concentration (E) : (0 ppm, 250 ppm, 500 ppm, and 750 ppm). Parameters observed were moisture content, vitamin C content, titratable acidity, total sugar, total soluble solid (TSS), hardness, weight loss, pulp to peel ratio, color score and organoleptic value of color, flavor, and texture.The results showed that maturity level and ethepon concentration had highly significant effect on moisture content, vitamin C content, titratable acidity, total sugar, TSS, hardness, weight loss, pulp to peel ratio, color score, organoleptic value of color, flavor, and texture. Interaction of the two factors had highly significant effect on hardness and  texture. The 85-90% maturity of barangan banana and 750 ppm concentration of ethepon produced the best quality of banana at three days storage. Keywords: barangan banana, ethepon concentration, maturity level